A NEW SPECIES OF BRACHYPHYLLUM FROM THE CRATO FORMATION (LOWER CRETACEOUS), ARARIPE BASIN, BRAZIL (Ameghiniana, 2020)
The Araripe Basin, located on the Northeast of Brazil, contains many fossils. Among these, the gymnosperms stand out, specially species of the fossil taxon Brachyphyllum. It encompasses conifer shoots with helically arranged scale-like, adpressed leaves whose length does not exceed the width. This foliage morphotype was widely distributed during the Mesozoic Era and species accomodated in this genus can be attributed to different families if their anatomical characters are taken into consideration. In the Araripe basin, specifically in the Crato and Romualdo formations, B. obesum is frequentlly found and was attributed to the family Araucariaceae based on leaf epidermal and xylem characters. In this work, we describe the new species from the Crato Formation (Lower Cretaceous), Brachyphyllum sattlerae sp. nov., based on the following morphological and anatomical features: submain shoots with lateral branches oppositely disposed and almost exclusively decussately arranged leaves; scarious leaf margins; rugose abaxial leaf surfaces; non-papillate epidermal cells; stomata distributed in longitudinal rows except close to the leaf margins and scarce at the leaf base; stomatal openings obliquely oriented; and hypodermis with a sinuous pattern around the substomatal chamber. Some of these features are distinctive of Araucariaceae, which indicates that B. sattlerae sp. nov. also belongs to this family.